Understanding Hip Contact Stress Based on Types of Physical Activity: A Systematic Review - Arief Indra Perdana Prasetya; Muhammad Imam Ammarullah; Tri Indah Winarni; Adriyan Pramono; Jamari Jamari; Tunku Kamarul; Ardiyansyah Syahrom (Health Science Reports)
ABSTRACT Background and Aims High contact stresses involving the hip have been shown to increase the risk of developing hip osteoarthritis (OA). Although several risk factors have been identified for OA, a holistic approach to predicting contributed factors toward increased hip contact stresses have not been explored. This study was conducted to comprehensively understand the effects of physical activity on high hip contact stress as predisposing factors of OA. Methods The protocol of this systematic review was registered in PROSPERO with registration number CRD42022296638 and conducted based on PRISMA guidelines. Full articles that matched our inclusion criteria were selected using PubMed, Web of Science, and Scopus search engines and keywords such as “hip contact stress,” “hip contact force,” and/or “hip contact pressure.” Category of factors, experimental design, results of the study, and evidence from each article were analyzed. Results In total 7972 papers were screened, identified, and reviewed. Two independent authors read the collected fulltext of eligible articles resulting in 21 papers that fulfilled the inclusion criteria of this systematic review. Conclusion Types of physical activity (n = 21) have correlation with high hip joint contact stress in various manner. Based on the research findings obtained from various inclusion papers, it can be broadly concluded that the more intense the physical activity, such as running and stair climbing, the greater the impact on the increase in hip contact stress values. However, the reviewed studies vary in their methods. This finding suggested that this area is not well investigated and warrants future research.